2018
DOI: 10.3171/2017.6.jns162398
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antitumor activity by using 5-ALA–mediated sonodynamic therapy to induce apoptosis in malignant gliomas: significance of high-intensity focused ultrasound on 5-ALA-SDT in a mouse glioma model

Abstract: ABBREVIATIONS DCFH-DA = dichlorodihydrofluorescein diacetate; DPBS = Dulbecco phosphate-buffered saline; FBS = fetal bovine serum; FUS = focused ultrasound; GSL = glioma stemlike; HIFU = high-intensity focused ultrasound; IP = intraperitoneal; NSC = neural stem cell; PDT = photodynamic therapy; PFA = paraformaldehyde; PpIX = protoporphyrin IX; ROS = reactive oxygen species; SDT = sonodynamic therapy; TBS = Tris-buffered saline; US = ultrasound; 5-ALA = 5-aminolevulinic acid; 5-ALA-SDT = 5-ALA-mediated SDT. OBJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 23 publications
4
32
1
Order By: Relevance
“…5-Aminolevulinic acid (5-ALA) can be utilized as a sensitizer for photodynamic and sonodynamic therapies. The generation of ROS contributes to the anti-cancer effects of these 5-ALA-based therapies [ 214 , 215 ]. Moreover, the expression of miRNAs can be changed by 5-ALA-based therapies.…”
Section: Tumor-suppressive Mirnas Induced By Phytochemicals Currenmentioning
confidence: 99%
“…5-Aminolevulinic acid (5-ALA) can be utilized as a sensitizer for photodynamic and sonodynamic therapies. The generation of ROS contributes to the anti-cancer effects of these 5-ALA-based therapies [ 214 , 215 ]. Moreover, the expression of miRNAs can be changed by 5-ALA-based therapies.…”
Section: Tumor-suppressive Mirnas Induced By Phytochemicals Currenmentioning
confidence: 99%
“…FUS is able to deeply and specifically penetrate brain tissue and to excite sonosensitizer only in the target area. Combining the specificity of 5-ALA accumulation in some types of tumors to the specificity of FUS insonation is possible to obtain necrosis and apoptosis only in the target volume [98]. Numerous studies demonstrated the efficacy in various cancers also comprising malignant glioma [98][99][100].…”
Section: Sonodynamic Therapymentioning
confidence: 99%
“…Combining the specificity of 5-ALA accumulation in some types of tumors to the specificity of FUS insonation is possible to obtain necrosis and apoptosis only in the target volume [98]. Numerous studies demonstrated the efficacy in various cancers also comprising malignant glioma [98][99][100]. Satoshi Suehiro et al [98] studied the combined application of 5-ALA and FUS demonstrating effective cytotoxicity towards glioma cells thus resulting in prolonged survival of tumor-bearing mice.…”
Section: Sonodynamic Therapymentioning
confidence: 99%
See 2 more Smart Citations